2022
DOI: 10.3390/biology11091284
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Individual Penalties According to Gender and Weight Categories of Elite Judo Athletes from Four World Championships

Abstract: Background: This research aimed to compare individual penalties by gender and weight categories in judo from the Judo World Championships (WC): Budapest—2017, Baku—2018, Tokyo—2019 and Budapest—2021 in all individual weight categories for females and males. Methods: Data were collected by notational analysis of 2041 penalty videos for females and 3473 penalty videos for males (total n = 5514). All individual penalties—Shido 1, 2, 3 and Hansoku Make (direct disqualification) were analysed by the Pearson chi-squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…n fact, in World Championships the most common prohibited actions were non-combativity and avoid-grip [ [21] , [22] ]. Furthermore, the number of penalties differs by weight division, as lighter athletes (especially 52 kg and 57 kg) commit a greater number of excessively defensive penalties, such as head escape, holding the same side, false attack, defensive posture and avoid-grip [ 22 ]. These data confirm that weight divisions can behave differently from the rules of competitive judo and therefore should be analyzed separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…n fact, in World Championships the most common prohibited actions were non-combativity and avoid-grip [ [21] , [22] ]. Furthermore, the number of penalties differs by weight division, as lighter athletes (especially 52 kg and 57 kg) commit a greater number of excessively defensive penalties, such as head escape, holding the same side, false attack, defensive posture and avoid-grip [ 22 ]. These data confirm that weight divisions can behave differently from the rules of competitive judo and therefore should be analyzed separately.…”
Section: Discussionmentioning
confidence: 99%
“…In combats from the 2017 World Judo Championship, the 48 kg category scored more frequently performing techniques involving turning action, forward throw, and two supporting feet (e.g., o-goshi, koshi-guruma, seoi-nage, sode-tsuri-komi-goshi , and seoi-otoshi ) [ 25 ]. Moreover, the 48 kg category received more penalties related to holding the sleeve ends in various competitions [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may have stemmed from the fact that many complex motoric and psychological abilities affect judo performance. Also, there have been numerous changes in judo competition rules and thus match duration and content since the development of SJFT [ 55 , 56 , 57 , 58 , 59 ]. In line with these changes, judo athletes’ physiological characteristics have also changed [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, regarding the penalties committed in the 2020 cycle, Balci and Ceylan (2020) analyzed the 2018–2019 senior world judo championships and found that the most committed prohibited actions in combat were non-combativity (common for those who held the grip without making attacks) and avoid grip (common for those who spent a lot of time in the approach phase). Kajmovic et al (2022) carried out a study that analyzed 2041 penalties committed by female judoka from competitions between 2017 and 2021. They identified that the main penalties were non-combativity (41.6%), avoid grip (16.2%) and false attack (15%).…”
Section: Discussionmentioning
confidence: 99%